Grass 2 Cash @Scale Project: Central Kenya regional multistakeholder workshop report - Binge, Brenda; Sibiko, Kenneth W; Muthomi, Fredrick; Kipkosgei, Solomon; Mwendia, Solomon; Ohmstedt, Uwe; Notenbaert, An (2022)
This report details the proceedings of the Grass 2 Cash @Scale project multistakeholder meeting, organized by the Alliance of Bioversity International and CIAT at Meru Slopes Hotel, Meru, on March 8-9, 2022. This regional workshop included 22 participants from Uasin-Gishu and Meru Counties, featuring a diverse mix of stakeholders such as researchers, dairy cooperative officials, farmers, seed companies, and livestock department representatives. The meeting aimed to develop a common understanding of the project objectives, refine the Theory of Change, validate monitoring and learning protocols, and draft an activity plan. The workshop combined open plenary and breakout sessions, with participants grouped by expertise to discuss different impact pathways, ensuring interactive and participatory discussions.